2007
DOI: 10.1158/1078-0432.ccr-06-2454
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Anticarcinoma Activity of an Anti-erbB2 Recombinant Immunotoxin by the Addition of an Anti-EpCAM sFv

Abstract: Purpose: erbB2, the product of the Her2-neu gene, is a well-established therapeutic target for antibody-based biologicals, but anti-erbB2 antibody-toxin fusion proteins are limited in their activity. The goal of this study was to determine if genetically adding an sFv targeting epithelial cell adhesion molecule (EpCAM) to an anti-Her2 sFv immunotoxin would result in enhanced antitumor activity. Experimental Design: In vitro studies were done in which the new bispecific immunotoxin DTEpCAM23 was compared with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 50 publications
(42 reference statements)
0
43
0
Order By: Relevance
“…Another bispecific immunotoxin simultaneously targeted EpCAM and erbB2, resulting in a hybrid that again had significantly greater activity against the two monomeric immunotoxins. Unlike DTEGF13, internalization studies of DTEpCAM/anti-erbB2 hybrid revealed a higher level of internalization with the bispecific immunotoxin rather than the monomeric immunotoxin (43). A bispecific immunotoxin was reported that selectively and simultaneously targeted human CD22 and CD19 on B cells and was effective in the therapy of systemic B-cell malignancy in a scid/hu mouse model (12).…”
Section: Discussionmentioning
confidence: 99%
“…Another bispecific immunotoxin simultaneously targeted EpCAM and erbB2, resulting in a hybrid that again had significantly greater activity against the two monomeric immunotoxins. Unlike DTEGF13, internalization studies of DTEpCAM/anti-erbB2 hybrid revealed a higher level of internalization with the bispecific immunotoxin rather than the monomeric immunotoxin (43). A bispecific immunotoxin was reported that selectively and simultaneously targeted human CD22 and CD19 on B cells and was effective in the therapy of systemic B-cell malignancy in a scid/hu mouse model (12).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-EpC has been reported to be of therapeutic efficacy in several types of human cancer (35,(44)(45)(46)(47)(48)(49). The most striking effect was observed with a bispecific antibody on ascites production by ovarian cancer (46).…”
Section: The Tumor Growth -Promoting Features Of Epc Rely On the Assomentioning
confidence: 99%
“…33 An impressive array of similar agents has been designed and tested using bispecific scFvs against EpCAM, various growth-factor and cytokine receptors, as well as an urokinase-type plasminogen activator receptor (uPAR), to import toxic cargo into various types of human cancer cells in culture and in mice xenografted with human cancer tissues. [34][35][36][37][38] For most of these agents, investigators have shown that the dualtargeting proteins had more potent anti-cancer activity than the corresponding mono-targeting control agents. We are not aware, however, of any studies attempting to demonstrate directly that the dual-targeting agent indeed preferentially eliminated antigen dp over sp cells when both were present in the same reaction mixture, mimicking the simultaneous presence of both types of cells in an infiltrated cancerous tissue.…”
Section: Introductionmentioning
confidence: 99%